We are now beginning our descent - Meek, James 1962- (Canongate, 2008)
Like the world around him, at the dawn of the twenty-first century, Adam Kellas' life is showing distinct signs of cracking apart. Against his better judgement, Kellas--divorced, unstable, spurned by his lover and by the world of letters--accepts a war assignment from his newspaper. It is the beginning of a journey which takes him from the mountains of Afghanistan to the elegant dinner tables of north London, the marshlands of the American South and, ultimately, to the darkest realms of the human imagination. Only the memory of the beautiful, elusive Astrid, a fellow reporter in Afghanistan, offers him the possibility of hope.
Keywords: War correspondents -- Fiction; Fiktionale Darstellung